Implementing basic e-learning tools into an undergraduate taxation curriculum. Issue 3 (8th August 2016) - van Oordt, T; Mulder, Ingrid
Abstract : Purpose: Educators in the accounting discipline are faced with the challenge of finding innovative ways to accommodate the flexible learning styles of Millennial students, utilising 'in classroom/contact time' effectively and decreasing transactional distance between students and educators in large classes. In an attempt to address these challenges, this paper describes the implementation of basic e-learning tools (podcasts, vodcasts and voice-over-PowerPoint) as supplementary and substitutional tools in an undergraduate taxation curriculum. The tools were implemented as part of a student-centred approach to the facilitation of learning, embedded in the Blended Learning Theory. The paper reports on students' use and experience of various basic e-learning tools, as well as the impact of the use of these tools on student performance. Design/methodology/approach: An action research methodology was followed and data was collected by way of a voluntary, descriptive student survey, and student class lists. A total of 387 students completed the survey. Findings: Students appear to have access to devices and data to use e-learning tools. They perceive these tools as helpful study aids and prefer synchronous, substitutional tools. Use of the tools does not have a significant impact on performance; however it does appear to have a positive impact on the learning environment and student engagement. Originality/value: The results of the study may be of benefit to educators and curriculum designers who are responsible for reviewing and updating the content delivery methods of undergraduate taxation curricula in large classes with diverse student populations. These results add to the limited body of knowledge on the implementation of basic e-learning tools in a South African accounting education setting.